Conservative & Operative Management of Tuberculous Spondylitis in Children - Teuku Arief Dian1, Komang Agung Irianto2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Tuberculosis is a deadly disease worldwide. Tuberculosis usually occurs in the lung, but there are other tuberculosis most commonly afflicted by the patient and involves the spine and is called tuberculosis of bones and joints. Management of tuberculous spondylitis is conservative and operative. Aim: This study aimed to compare the results of conservative and operative therapy in the management of tuberculous spondylitis in children. Methods: The sample used was teaching with tuberculous spondylitis in Dr. Soetomo General Hospital who underwent operative and conservative therapy that became group 1 and group 2. Inclusion criteria included patients aged <18 years old, suffering from tuberculous spondylitis by conservative or operative therapy in Dr. Soetomo Hospital. Results: In patients receiving conservative therapy, the Visual analog scale (VAS) decreased significantly (p = 0.001), while frankle improved but not significantly (p = 0.157). Cobb’s angle of patients receiving conservative therapy increased significantly (p = 0.007). Patients who received operative therapy showed significant improvement of VAS and Frankle (p = 0.001 and p = 0.011). The patient’s Cobb’s angle after surgery decreased but it was not significant (p = 0.575). Conclusion: The role of surgical action has an important role in the treatment of tuberculous spondylitis and gives better results than conservatives in patients with pain, neurological deficits and Cobb’s angle progression.